A preparation method for keratinized gingival repair stent
By using biomicrosphere active powder and protein slurry to prepare loose surface raw liquid in the preparation of keratinized gingival repair materials, and lyophilized, cross-linked and stage temperature-controlled treatment, the problems of uneven collagen dispersion and low cell adhesion rate were solved, and a large-effect keratinized gingival repair scaffold with porous structure and good antibacterial properties were prepared.
Patent Information
- Application Number
- CN202411133047.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-19
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-08-19
AI Technical Summary
In the prior art, when preparing keratinized gingival repair materials, collagen is unevenly dispersed, resulting in poor repair effect, low cell adhesion rate, and the oral environment is prone to infection with bacteria, affecting the repair effect.
Biomicrosphere active powder is used to disperse it in the protein slurry, and the loose surface raw liquid is prepared, and it is injected into the mold to freeze dry to form a prototype scaffold. It is then cross-linked in the aqueous cross-linking agent solution, and is subjected to stage temperature control and re-treatment, washed and dried to form a keratinized gingival repair scaffold with loose surface and dense surface.
The keratinized gingival repair scaffold prepared by this method has a porous sponge structure, which promotes cell attachment and growth, has good antibacterial properties and the ability to promote bone growth, can effectively maintain and regulate the pH environment in the oral cavity, and inhibit the growth of harmful bacteria.
Smart Images

Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of biomedical materials, and in particular relates to a method for preparing a keratinized gingival repairing bracket. Background Art
[0002] The gums are divided into three parts: the gingival papilla, the attached gingiva and the free gingiva. Among them, the attached gingiva and the free gingiva are continuous. The attached gingiva is the gingival tissue with keratinized surface attached to the tooth root or alveolar bone through connective tissue fibers. It is pink in color. The free gingiva wraps around the neck of the tooth and is not attached to the tooth surface. It is a semi-lunar continuous curve. The attached gingiva and the free gingiva are collectively called keratinized gingiva. It is reported that keratinized gingiva is closely related to oral health. When the width of keratinized gingiva is less than 2mm, even if there are no obvious symptoms such as plaque, the gingiva is still inflamed, and the risks of bleeding index and periodontal pocket depth in this area will increase significantly.
[0003] Patent No. CN110368525B provides an oral membrane for attached gingival reconstruction and a preparation method thereof, which is obtained by directly freeze-drying the collagen acid solution of de-terminated type I collagen and then rolling it. However, when the collagen acid solution is directly freeze-dried for use, there is a risk of uneven collagen dispersion, resulting in poor repair effect after implantation in the oral cavity. At the same time, although the aforementioned technology uses rolling to make the freeze-dried material denser, it may improve the problem of uneven collagen dispersion to a certain extent, but rolling makes the material denser and smoother, which also reduces the cell attachment rate and worsens the effect of cell growth into the tissue. In addition, wounds in the oral environment are susceptible to bacterial infection, which will further affect the repair effect of pure protein implant materials. Summary of the invention
[0004] In order to solve the above problems, the first aspect of the present invention provides a method for preparing a keratinized gingival repair scaffold, and the preparation method is as follows:
[0005] S1. The active powder of biological microspheres is dispersed in the protein slurry to prepare a loose surface stock solution;
[0006] S2. The loose surface stock solution is injected into a stainless steel mold covered with acellular matrix material, and the height of the loose surface stock solution in the mold is controlled to be 0.8-2.4 mm, and freeze-dried to obtain a prototype scaffold;
[0007] S3. The prototype scaffold is immersed in an aqueous solution of a crosslinking agent for crosslinking;
[0008] S4. The cross-linked prototype scaffold is subjected to stage-by-stage temperature control reprocessing, water washing, and drying to obtain the result.
[0009] As a preferred embodiment, the biomicrosphere active powder is selected from one or more of silver-doped bioglass, magnesium-doped bioglass, and zinc-doped bioglass.
[0010] Preferably, the biomicrosphere active powder is silver-doped bioglass and / or magnesium-doped bioglass.
[0011] When the bio-microsphere active powder is a mixture of silver-doped bio-glass and magnesium-doped bio-glass, the weight ratio of the silver-doped bio-glass to the magnesium-doped bio-glass in the bio-microsphere active powder is (2.2-5.6): (0.3-1.4).
[0012] The preparation method of silver-doped bioglass is as follows: add bioglass to 0.06-0.15 mol / L AgNO3 aqueous solution, the mass volume ratio of bioglass and AgNO3 aqueous solution is (0.1-5 g): 250 mL, keep in a light-proof 55-60°C constant temperature water bath for 8-36 hours, filter, take the filter residue, dry the filter residue, grind, and sieve to obtain the silver-doped bioglass.
[0013] Due to the particularity of the oral environment, oral implant materials need to consider the antibacterial properties of the implant materials. At present, many products achieve broad-spectrum antibacterial properties by adding non-irritating antimicrobial peptides. However, the strong broad-spectrum antibacterial activity of antimicrobial peptides usually kills the symbiotic bacteria of the host, including beneficial bacteria such as peptostreptococci. Studies have found that metal nanoparticles, especially silver nanoparticles, can specifically inhibit the growth of other bacteria, but have no obvious inhibitory effect on the proliferation of peptostreptococci. Therefore, in order to make the repair stent have good antibacterial properties, the present invention introduces silver-doped bioglass and / or magnesium-doped bioglass.
[0014] As a preferred embodiment, the bioglass comprises SiO2, CaO and P2O5, wherein the content of CaO is 16-30wt%.
[0015] Preferably, the bioglass comprises SiO2, CaO and P2O5, wherein the content of CaO is 16-25wt%.
[0016] As a preferred embodiment, the particle size distribution range of the biological microsphere active powder is 0-100 µm.
[0017] As a preferred embodiment, the protein slurry is atelocollagen type I slurry or silk fibroin slurry.
[0018] In the atelocollagen type I slurry, the mass fraction of atelocollagen type I is 0.2-2%.
[0019] In the atelocollagen type I slurry, the mass fraction of atelocollagen type I is 0.5-1.5%.
[0020] In the silk fibroin slurry, the mass fraction of silk fibroin is 0.2-2%.
[0021] In the silk fibroin slurry, the mass fraction of silk fibroin is 0.5-1.5%.
[0022] The protein slurry is obtained by dispersing atelocollagen type I or silk fibroin in water.
[0023] As a preferred embodiment, in the step S1, the content of the active powder of biological microspheres in the loose surface stock solution is 0.01-1wt%.
[0024] In step S2, the acellular matrix material is selected from any one of porcine bladder basement membrane, porcine small intestinal submucosa, bovine pericardium or acellular dermal matrix.
[0025] As a preferred embodiment, in step S3, the cross-linking agent is selected from any one or more of glutaraldehyde, carbodiimide or genipin.
[0026] In step S3, the concentration of the crosslinking agent in the crosslinking agent aqueous solution is 0.1-10 wt %.
[0027] As a preferred implementation, in step S4, the stage temperature control reprocessing includes five stages.
[0028] As a preferred implementation, the five stages are specifically:
[0029] Stage temperature control reprocessing stage 1: placing the cross-linked prototype scaffold obtained in step S3 in a vacuum drying oven, evacuating the air, raising the temperature to 35-50° C., and keeping the temperature for 30-60 min;
[0030] Stage temperature control and reprocessing stage 2: heating to 90-100℃, keeping warm for 2-6h;
[0031] Stage temperature control and reprocessing stage 3: heating to 120-140℃, keeping warm for 2-4h;
[0032] Stage temperature control and reprocessing stage 4: cool down to 50-100℃, keep warm for 30-90min;
[0033] Stage 5 temperature control and reprocessing: After cooling to 25-30℃, take out.
[0034] Preferably, in step S4, the stage temperature control reprocessing includes five stages, specifically:
[0035] Stage temperature control reprocessing stage 1: Place the cross-linked prototype scaffold obtained in step S3 in a vacuum drying oven, evacuate, raise the temperature to 35-50°C at 2-3°C / min, and keep the temperature for 30-60min;
[0036] Stage temperature control and reprocessing stage 2: heating to 90-100℃ at 2℃ / min, keeping warm for 2-6h;
[0037] Stage temperature control and reprocessing stage 3: heating to 120-140℃ at 5℃ / min, keeping warm for 2-4h;
[0038] Stage temperature control and reprocessing stage 4: cool down to 50-100℃ at 2-5℃ / min, keep warm for 30-90min;
[0039] The fifth stage of stage temperature control and reprocessing: cool down to 25-30℃ at 2-5℃ / min and then take out.
[0040] Generally speaking, after using a cross-linking agent to cross-link the material, it should be washed with water first, and the cross-linking agent should be washed away before subsequent operations. However, the inventor unexpectedly discovered in the experiment that the prototype scaffold after cross-linking with a cross-linking agent was not washed with water, but was further subjected to staged temperature control treatment, and then the cross-linking agent was washed away and dried, which could have a certain effect on the oral pH microenvironment with trauma. This may mean that it has a certain improvement effect on the problem of rapid changes in the local pH value around the implant and inhibition of bone growth caused by the degradation of the active powder of the biomicrospheres doped with metal nanoparticles. The inventor speculates that this may be because the prototype scaffold after cross-linking with a cross-linking agent is further subjected to staged temperature control treatment, which changes the free energy of the particle surface, causes the particles to aggregate and collide, affects the formation of the internal cross-linking network, and further affects the environmental changes caused by the degradation of the resulting material after implantation in the oral cavity. The above changes are particularly significant in the specific temperature control stage described in the present invention.
[0041] The second aspect of the present invention provides a keratinized gingiva repair scaffold prepared by the above preparation method, wherein the keratinized gingiva repair scaffold comprises a loose surface and a dense surface, and the diameter of the loose surface is 10-300 μm. Beneficial Effects
[0042] The keratinized gingival repair scaffold prepared by the preparation method of the present invention has a loose surface and a dense surface with different pore sizes. When in use, the loose surface of the porous sponge structure contacts the wound surface, which is conducive to the attachment and growth of tissue cells, and the dense surface can seal and protect the wound to a certain extent in an open healing environment. The obtained keratinized gingival repair scaffold can effectively maintain and regulate the pH environment in the oral cavity, inhibit bacteria and resist bacteria, and inhibit the growth of acid-producing bacteria such as Streptococcus mutans and bacteria with strong caries-causing properties. At the same time, it has the ability to stop bleeding, promote bone growth and periodontal ligament regeneration, and inhibit periodontal epithelial regression.
[0043] While effectively repairing keratinized gingiva, it increases the bonding strength between tissue and bone, promotes bone growth, and overcomes the problem that the degradation of the active powder of biomicrospheres doped with metal nanoparticles leads to rapid changes in the local pH value around the implant, which inhibits bone growth.
[0044] After absorbing water and swelling, it still retains about 70% of its volume after undergoing 99 cycles of loading. It can effectively resist the complex mechanical forces in the oral cavity and maintain the stability of tissue volume for a sufficiently long time during the healing process after implantation. DETAILED DESCRIPTION
[0045] The materials used in the examples are all commercially available, among which atelocollagen type I was purchased from Amyjet, model number PureCol, bovine atelocollagen solution (ABM-5005-100ML), and silk fibroin were purchased from Jianchu Biotechnology. Example 1
[0046] This example provides a method for preparing a keratinized gingival repair scaffold, and the preparation method is as follows:
[0047] S1. The bio-microsphere active powder is dispersed in the protein slurry to prepare the loose noodle stock solution.
[0048] The protein slurry is 1% by weight of atelocollagen type I slurry, the biological microsphere active powder is silver-doped bioglass, and the content of the biological microsphere active powder in the loose surface stock solution is 0.5wt%.
[0049] The preparation method of silver-doped bioglass is as follows: add bioglass (purchased from Hanno Biotechnology, model S53P4, article number CER-0042, the bioglass includes SiO2, CaO and P2O5, wherein the content of CaO is 18-22wt%) to 0.09mol / L AgNO3 aqueous solution, the mass volume ratio of bioglass and AgNO3 aqueous solution is 1g:250mL, keep in a light-proof constant temperature water bath at 60°C for 12h, filter, take the filter residue, dry the filter residue, grind it, and pass it through a 200-mesh sieve to obtain silver-doped bioglass with a particle size distribution range of 0-80µm.
[0050] S2. The loose surface stock solution is injected into a stainless steel mold covered with acellular matrix material (porcine bladder basement membrane, sourced from Zhuoruan Medical Technology (Suzhou) Co., Ltd.), and the height of the loose surface stock solution in the mold is controlled to be 2 mm. After freeze-drying, a prototype scaffold is obtained.
[0051] S3. The prototype scaffold was immersed in a 2wt% glutaraldehyde aqueous solution for cross-linking for 12h;
[0052] S4. The cross-linked prototype scaffold is subjected to stage-by-stage temperature control reprocessing, water washing, and drying to obtain the result.
[0053] Stage temperature control reprocessing includes five stages, specifically:
[0054] Stage temperature control reprocessing stage 1: Place the cross-linked prototype scaffold obtained in step S3 in a vacuum drying oven, evacuate, and heat to 45°C at 2°C / min, and keep warm for 40 minutes;
[0055] Stage temperature control reprocessing stage 2: heating to 100°C at 2°C / min and keeping warm for 2h;
[0056] Stage temperature control reprocessing stage 3: heating to 130°C at 5°C / min and keeping warm for 3h;
[0057] Stage temperature control and reprocessing stage 4: cooling to 70°C at 2°C / min, keeping warm for 60min;
[0058] The fifth stage of stage temperature control reprocessing: cool down to 25℃ at 2℃ / min and then take out. Example 2
[0059] This example provides a method for preparing a keratinized gingival repair scaffold. The difference from Example 1 is that the biomicrosphere active powder is a mixture of silver-doped bioglass and magnesium-doped bioglass (purchased from Kunshan Overseas Chinese Science and Technology Materials Co., Ltd., model 13-93, the bioglass includes SiO2, CaO, P2O5 and MgO, wherein the CaO content is 20wt%, and the MgO content is 5wt%). In the biomicrosphere active powder, the weight ratio of silver-doped bioglass to magnesium-doped bioglass is 3.2:0.8. Example 3
[0060] This example provides a method for preparing a keratinized gingival repair scaffold. The difference from Example 1 is that the protein slurry is a silk fibroin slurry with a mass fraction of 1.5%.
[0061] Comparative Example 1
[0062] This example provides a method for preparing a keratinized gingival repair scaffold. The difference from Example 1 is that the preparation method of silver-doped bioglass is as follows: add bioglass (purchased from Kunshan Overseas Chinese Science and Technology Materials Co., Ltd., model 58s, the bioglass includes SiO2, CaO and P2O5, wherein the CaO content is 36wt%) to 0.1mol / L AgNO3 aqueous solution, the mass volume ratio of bioglass to AgNO3 aqueous solution is 0.8g:250mL, keep in a light-proof constant temperature water bath at 60°C for 12h, filter, take the filter residue, dry the filter residue, grind it, and pass it through a 200-mesh sieve to obtain silver-doped bioglass with a particle size distribution range of 0-80µm.
[0063] Comparative Example 2
[0064] This example provides a method for preparing a keratinized gingival repair scaffold. The difference from Example 1 is that step S4 is: directly washing and drying the cross-linked prototype scaffold obtained in step S3.
[0065] Comparative Example 3
[0066] This example provides a method for preparing a keratinized gingival repair scaffold. The difference from Example 1 is that step S4 specifically includes placing the prototype scaffold cross-linked in step S3 in a vacuum drying oven, evacuating the air, heating the oven to 100°C at 2°C / min, keeping the temperature for 7 minutes, taking out, washing with water, and drying the scaffold.
[0067] Comparative Example 4
[0068] This example provides a method for preparing a keratinized gingival repair scaffold, and the preparation method is as follows:
[0069] S1. The bio-microsphere active powder is dispersed in the protein slurry to prepare the loose noodle stock solution.
[0070] The protein slurry is 1% by weight of atelocollagen type I slurry, the biological microsphere active powder is silver-doped bioglass, and the content of the biological microsphere active powder in the loose surface stock solution is 0.5wt%.
[0071] The preparation method of silver-doped bioglass is as follows: add bioglass (purchased from Hanno Biotechnology, model S53P4, article number CER-0042, the bioglass includes SiO2, CaO and P2O5, wherein the content of CaO is 18-22wt%) to 0.09mol / L AgNO3 aqueous solution, the mass volume ratio of bioglass and AgNO3 aqueous solution is 1g:250mL, keep in a light-proof constant temperature water bath at 60°C for 12h, filter, take the filter residue, dry the filter residue, grind it, and pass it through a 200-mesh sieve to obtain silver-doped bioglass with a particle size distribution range of 0-80µm.
[0072] S2. The loose surface stock solution is injected into a stainless steel mold covered with acellular matrix material (porcine bladder basement membrane, sourced from Zhuoruan Medical Technology (Suzhou) Co., Ltd.), and the height of the loose surface stock solution in the mold is controlled to be 2 mm. After freeze-drying, a prototype scaffold is obtained.
[0073] S3. The prototype scaffold is subjected to stage temperature control reprocessing, water washing, and drying.
[0074] Stage temperature control reprocessing includes five stages, specifically:
[0075] Stage temperature control reprocessing stage 1: Place the prototype scaffold obtained in step S2 in a vacuum drying oven, evacuate, raise the temperature to 45°C at 2°C / min, and keep the temperature for 40 minutes;
[0076] Stage temperature control reprocessing stage 2: heating to 100°C at 2°C / min and keeping warm for 2h;
[0077] Stage temperature control reprocessing stage 3: heating to 130°C at 5°C / min and keeping warm for 3h;
[0078] Stage temperature control and reprocessing stage 4: cooling to 70°C at 2°C / min, keeping warm for 60min;
[0079] The fifth stage of stage temperature control reprocessing: cool down to 25℃ at 2℃ / min and then take out.
[0080] Test Results
[0081] 1. Cyclic compression performance: The keratinized gingival repair scaffolds prepared in Examples 1-3 and Comparative Examples 1-4 were immersed in a phosphate buffer solution at 37°C and pH=7.4 for 2 h, and then the samples were measured using a compressor for 99 cycles between 0.5 and 12.1 kPa. The initial thickness percentage W (%) of the sample after 99 cycles of loading relative to the first loading was calculated. , W represents the percentage of the initial thickness of the sample after cyclic loading relative to the first loading, w1 represents the initial thickness of the sample, unit: mm; w2 represents the thickness of the sample after 99 cycles of loading, unit: mm. The results are shown in Table 1.
[0082] Table 1
[0083] Example Thickness percentage W(%) Example 1 82.1 Example 2 79.9 Example 3 80.4 Comparative Example 1 64.2 Comparative Example 2 42.7 Comparative Example 3 71.4 Comparative Example 4 No complete form
[0084] In order to maintain the volume of the keratinized gingival area, the sample must be able to withstand the complex mechanical forces caused by chewing, tongue movement, speech and tooth movement. After swelling with water, the keratinized gingival repair scaffold obtained by the present invention still has a volume retention of about 70% after 99 cycles of loading, which can well resist the complex mechanical forces in the oral cavity and maintain the stability of tissue volume for a sufficiently long time during the healing process after implantation.
[0085] 2. Study on alveolar bone with gingival defect model: A beagle dog alveolar bone with gingival defect model was made (part of the mandibular alveolar bone and gingival tissue were removed). The keratinized gingival width of the target point before modeling was measured to be 7 mm, and the keratinized gingival width immediately after modeling was 0.95 mm. The bone defect filling material (purchased from Geistlich Pharma AG) was filled into the bone defect, and the keratinized gingival repair scaffolds obtained in Example 1 and Comparative Example 2 were covered thereon, and a blank control group (without any bone defect filling material and keratinized gingival repair material) was set up. The width of the keratinized gingiva at the modeling site of the mandibular alveolar bone of the beagle dogs was recorded on the 3rd day, 1 month, 3 months and 6 months after surgery, and whether inflammation occurred at the implantation site (mild inflammation—mild edema, no bleeding; moderate inflammation—obvious edema, red color, and spontaneous bleeding tendency) and whether the filled keratinized gingival repair scaffold was displaced were observed. Cone beam CT (CBCT) test was performed to record the alveolar bone height (measured three times and the average value was taken), which was recorded as the height of the new alveolar bone. The height relative to the defect at 3 months and 6 months after surgery was calculated, and the results are shown in Table 2:
[0086] Table 2
[0087]
[0088] During the experiment, the beagle dogs maintained good physical and mental conditions. It can be seen from Table 2 that the keratinized gingival scaffold obtained by the present invention can increase the binding force between tissue and bone while quickly and effectively repairing the keratinized gingiva. In addition, it can be seen that the keratinized gingival repair scaffold obtained by the present invention has good binding force with the repair soft tissue part and the bone defect repair material, and is not easy to shift, which also shows that the keratinized gingival repair scaffold itself has good stability, and can also improve the stability of the bone defect repair material.
[0089] 3. Oral pH environment: The oral pH value of a healthy dog is about 7.5-8.7, which is weakly alkaline. For the beagle oral model of the aforementioned performance test 2, the local pH of the modeling site was tested on the first day after surgery, 2 weeks after surgery, and one month after surgery. The results showed that the local pH of the modeling site of the keratinized gingival repair scaffold implanted in Example 1 was weakly alkaline on the first day after surgery, 2 weeks after surgery, and one month after surgery, which also matches the result that there was basically no inflammation (i.e., only mild inflammation occurred on the third day after surgery). The material prepared in Example 1 can effectively improve the oral pH microenvironment with trauma, inhibit the reproduction and growth of harmful oral bacteria, thereby reducing bacteria or acid produced by bacteria, so that the oral cavity maintains a healthy environment; the local pH of the modeling site of the keratinized gingival repair scaffold implanted in comparative example 2 and the blank control was close to acidic on the third day after surgery and 2 weeks after surgery, which also matches the result that moderate inflammation occurred on the third day after surgery.
Claims
1. A method for preparing a keratinized gingival repair scaffold, characterized in that: The preparation method is as follows: S1. The active powder of biological microspheres is dispersed in the protein slurry to obtain a loose surface stock solution; the active powder of biological microspheres is selected from one or more of silver-doped bioglass, magnesium-doped bioglass, and zinc-doped bioglass; S2. The loose surface stock solution is injected into a stainless steel mold covered with acellular matrix material, and the height of the loose surface stock solution in the mold is controlled to be 0.8-2.4 mm, and freeze-dried to obtain a prototype scaffold; S3. The prototype scaffold is immersed in an aqueous solution of a crosslinking agent for crosslinking; S4. The cross-linked prototype scaffold is subjected to stage temperature control, washed, and dried to obtain; In step S4, the stage temperature control reprocessing includes five stages, which are specifically: Stage temperature control reprocessing stage 1: placing the cross-linked prototype scaffold obtained in step S3 in a vacuum drying oven, evacuating the air, raising the temperature to 35-50° C., and keeping the temperature for 30-60 min; Stage temperature control and reprocessing stage 2: heating to 90-100℃, keeping warm for 2-6h; Stage temperature control and reprocessing stage 3: heating to 120-140℃, keeping warm for 2-4h; Stage temperature control and reprocessing stage 4: cool down to 50-100℃, keep warm for 30-90min; Stage 5 temperature control and reprocessing: After cooling to 25-30℃, take out.
2. The method for preparing the keratinized gingiva repair scaffold according to claim 1, characterized in that: The bioglass comprises SiO2, CaO and P2O5, wherein the content of CaO is 16-30wt%.
3. The method for preparing the keratinized gingiva repair scaffold according to claim 1 or 2, characterized in that: The particle size distribution range of the biological microsphere active powder is 0-100 μm.
4. The method for preparing the keratinized gingiva repair scaffold according to claim 1, characterized in that: The protein slurry is atelocollagen type I slurry or silk fibroin slurry.
5. The method for preparing the keratinized gingiva repair scaffold according to claim 1, characterized in that: In the step S1, the content of the active powder of biological microspheres in the loose surface stock solution is 0.01-1wt%.
6. The method for preparing the keratinized gingiva repair scaffold according to claim 1, characterized in that: In the step S3, the cross-linking agent is selected from any one or more of glutaraldehyde, carbodiimide or genipin.
7. A keratinized gingiva repair scaffold prepared by the preparation method of the keratinized gingiva repair scaffold according to claim 1, characterized in that: The keratinized gingival repair scaffold comprises a loose surface and a dense surface, and the diameter of the loose surface is 10-300 μm.
Citation Information
Patent Citations
An oral membrane for attached gingival reconstruction and its preparation method
CN110368525B
Double-functional-layer oral restoration membrane and preparation method thereof
CN105457107A
Collagen composite film for guiding tissue regeneration and preparation method and application thereof
CN107875454A
Cited By
Preparation method of oral keratinized gingival regeneration and repair stent and product thereof
CN121154934A